2018
DOI: 10.1016/j.envsci.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural land management changes on surface water quality: A review of meso-scale catchment research

Abstract: Measuring the environmental impacts of agricultural practice is critical for policy formulation and review, including policies implemented to improve water quality. Here, studies that measured such impacts in surface waters of hydrologically diverse meso-scale catchments (1-100 km 2 ) were reviewed. Positive water quality effectswere measured in 17 out of 25 reviewed studies. Successful farm practices included improved landscape engineering, improved crop management and reductions in farming intensity. Positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 60 publications
(26 reference statements)
0
39
0
3
Order By: Relevance
“…Similar counterclockwise hystereses have been found in several catchments worldwide (Howden, Burt, Worrall, et al, ; Howden, Burt, Mathias, et al, ; Kelly et al, ; Kopacek et al, ; Stets et al, ; Van Meter et al, ; Van Meter & Basu, ; Viaroli et al, ). It must be noted that the 10‐year response time in Brittany catchments is a function not only of the catchment properties but also of the monitoring strategy deployed, as previous studies have shown that higher‐frequency sampling can detect shorter response times because they better capture “hot moments” of transport when fast responding flow paths are activated (Melland et al, ; Wall et al, ). N load remained below N surplus for all catchments and all dates (Figure ), indicating a negative mass balance at the catchment scale.…”
Section: Discussionmentioning
confidence: 99%
“…Similar counterclockwise hystereses have been found in several catchments worldwide (Howden, Burt, Worrall, et al, ; Howden, Burt, Mathias, et al, ; Kelly et al, ; Kopacek et al, ; Stets et al, ; Van Meter et al, ; Van Meter & Basu, ; Viaroli et al, ). It must be noted that the 10‐year response time in Brittany catchments is a function not only of the catchment properties but also of the monitoring strategy deployed, as previous studies have shown that higher‐frequency sampling can detect shorter response times because they better capture “hot moments” of transport when fast responding flow paths are activated (Melland et al, ; Wall et al, ). N load remained below N surplus for all catchments and all dates (Figure ), indicating a negative mass balance at the catchment scale.…”
Section: Discussionmentioning
confidence: 99%
“…The factor that adversely affects for water quality is primarily the human activity in the catchment area of the reservoir. Pollution can come from the living activity (Cheung et al 2003), agricultural activity (Melland et al 2018) and industrial activity (Dimitrova et al 1998), though most often the all types of anthropogenic pressure occur (Dassenakis et al 1998), and the environment is characterized by the comprehensive pollution (Rzetala et al 2011). However, it is worth emphasizing that the water flow through dam reservoirs often causes an improvement in its quality (Jagus and Rzetala 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The over-application of fertilizers damages the ecosystems on large spaces, including soil, water and underground aquifer layers [7]. The main problems associated with intensive agriculture are salinization, nitrification, pesticide contamination and excessive erosion that produce high concentrations of colloids in flowing waters [8].Significant emissions of atmospheric pollutants and long-range transport have affected large areas, while droplets formed in the atmosphere through the combination of water with the gases produced by burning fossil fuels cause acid rain that leads to the acidification of surface waters, especially of lakes [9].Society uses natural resources in a steadily increasing rate. Human influence on nature may cause adverse consequences leading to the disturbance of the natural balance [10,11].…”
mentioning
confidence: 99%
“…The over-application of fertilizers damages the ecosystems on large spaces, including soil, water and underground aquifer layers [7]. The main problems associated with intensive agriculture are salinization, nitrification, pesticide contamination and excessive erosion that produce high concentrations of colloids in flowing waters [8].…”
mentioning
confidence: 99%